Glioblastoma in a patient with tuberous sclerosis. (February 2019) - Azriel, Amit; Gogos, Andrew; Rogers, TeWhiti; Moscovici, Samuel; Lo, Patrick; Drummond, Katharine
Highlights: Tuberous sclerosis complex (TSC) is a multisystem, autosomal dominant disorder with a wide clinical spectrum. Reports of high grade primary brain tumors in patients with TSC are rare. TSC1/2 mutation has been identified in glioblastoma (GBM). Clinical and radiological re-assessment is indicated for new neurological signs or symptoms. Abstract: Tuberous sclerosis complex (TSC) is a multisystem, autosomal dominant disorder with a wide clinical spectrum. The most common brain tumor associated with TSC is the low grade subependymal giant cell astrocytoma. Reports of high grade primary brain tumors in patients with TSC are rare. TSC1/2 mutation has been identified in glioblastoma (GBM) even though it probably does not increase the overall risk for GBM in patients with TSC. We present a 58-year-old patient with known TSC, admitted for new neurological symptoms, diagnosed with a large heterogeneous tumor involving most of the corpus callosum. Stereotactic needle brain biopsy confirmed the diagnosis to be GBM. Five previously reported similar cases are reviewed, reflecting diversity in clinical and radiological findings and indicating that a high index of clinical suspicion must be maintained in patients with TSC.